1982
DOI: 10.1111/j.1365-2273.1982.tb01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital nasal masses: diagnosis and management

Abstract: One hundred and nine congenital nasal masses which presented to two children's hospitals over a 20 year period are reviewed. The diagnosis of the nasal mass is discussed with respect to age, mode of presentation, and site of the lesion, and a management protocol is advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 36 publications
0
47
0
1
Order By: Relevance
“…Even for intranasal gliomas, many surgeons considered the extranasal approach appropriate for mass removal because of the visualization of the base of the skull. 3,15,16 Here, we show that intranasal gliomas can be excised successfully at an early age without complications by endoscopic surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Even for intranasal gliomas, many surgeons considered the extranasal approach appropriate for mass removal because of the visualization of the base of the skull. 3,15,16 Here, we show that intranasal gliomas can be excised successfully at an early age without complications by endoscopic surgery.…”
Section: Discussionmentioning
confidence: 93%
“…2 In a recently published British review, nasal glioma is reported to account for 5 of 109 congenital nasal masses. 3 Sixty percent of cases of nasal glioma are extranasal, 30% are intranasal, and 10% are a combination of both sites. 4,5 The nasal glioma is a smooth, rubbery, and neural malformation.…”
mentioning
confidence: 99%
“…Schmidt was the first to present a comprehensive description of this lesion and coined the term glioma in 1900 [1]. According to Bradley et al nasal glioma is reported to account for five of 109 congenital nasal masses [2]. Nasal glial heterotopia is frequently diagnosed in newborn infants, but rarely found in adults.…”
Section: Introductionmentioning
confidence: 98%
“…2 According to Bradley et al nasal glioma is reported to account for five of 109 congenital nasal masses. 3 Clinically, 60% of nasal gliomas are extranasal, 30% are intranasal and 10% are mixed extraand intranasal. 4 Extranasal gliomas appear in or just lateral to the midline.…”
Section: Introductionmentioning
confidence: 99%